1989
DOI: 10.1002/jat.2550090303
|View full text |Cite
|
Sign up to set email alerts
|

Effect of four‐week repeated inhalation exposure to unconjugated azodicarbonamide on specific and non‐specific airway sensitivity of the guinea pig

Abstract: Reports of respiratory problems among industrial workers exposed repeatedly by inhalation to azodicarbonamide (ADA) raised concern that ADA might be a pulmonary sensitizer. We used a non-invasive method for measuring specific airway conductance to evaluate the potential for repeated inhalation of unconjugated ADA to cause specific or non-specific pulmonary sensitization in the guinea pig. Two groups of male Hartley guinea pigs were exposed 6 h/day, 5 days/week for 4 weeks to aerosolized ADA at 51 or 200 mg/m3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…tions used in the studies reported here (i.e., 100 and 200 mg/m3) suggests that the lung lesions in rats are not related to ADA exposure. In addition, two recent studies of acute and repeated inhalation exposure to ADA in guinea pigs did not report any evidence of airway irritation (Shopp, 1987) or a potential for sensitization to ADA (Gerlach et al, 1989). Pyelonephritis, renal tubular concretions, and intratubular renal crystals were noted after subchronic exposure of rats and mice to ADA by gavage, at levels of 2.5 g/kg body wt or greater per day.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…tions used in the studies reported here (i.e., 100 and 200 mg/m3) suggests that the lung lesions in rats are not related to ADA exposure. In addition, two recent studies of acute and repeated inhalation exposure to ADA in guinea pigs did not report any evidence of airway irritation (Shopp, 1987) or a potential for sensitization to ADA (Gerlach et al, 1989). Pyelonephritis, renal tubular concretions, and intratubular renal crystals were noted after subchronic exposure of rats and mice to ADA by gavage, at levels of 2.5 g/kg body wt or greater per day.…”
Section: Discussionmentioning
confidence: 89%
“…No lesions were noted in respiratory tract tissue of animals euthanized immediately after exposure or 24 hr later. Repeated exposure of guinea pigs to 51 or 200 mg ADA/m3 for 4 weeks did not result in either specific or nonspecific airway sensitization on inhalation challenge with ADA or aerosolized histamine, respectively (Gerlach et al, 1989). The objective of the studies reported here was to describe the toxic effects in rats and mice of inhalation exposure for 2 or 13 weeks to airborne concentrations of ADA as high as 200 mg/m3.…”
mentioning
confidence: 96%
“…It has been previously demonstrated that the values of SRaw, as measured by our system, are reasonably ac curate and reliable when compared with those mea sured by a pleural catheter technique [14,15]. There fore, it is proposed that our method mainly measures the changes in the lower airways, although the upper airways component may contribute in part.…”
Section: Discussionmentioning
confidence: 97%
“…Pulmonary function in unanesthetized guinea pigs was mea sured using a two-chambered, whole-body plethysmograph, which was described by Gcrlach et al [14] ( fig. 2).…”
Section: In Vivo Bronchoconstriction Experimentsmentioning
confidence: 99%
“…According to the authors, the observed erythematous reactions resulted from a foreign body reaction caused by azodicarbonamide. The exposure to azodicarbonamide by inhalation did not influence body weights or cause histopathological changes (Gerlach et al 1989). …”
Section: Sensitizing Effects On the Airwaysmentioning
confidence: 97%